DIFFERENCE IN HbA1c LEVEL BETWEEN BORONATE AFFINITY AND ION EXCHANGE-HIGH PERFORMANCE LIQUID CHROMATOGRAPHY METHOD IN DIABETIC PATIENT - Tuti Asryani; Ellyza Nasrul; Rikarni Rikarni; Tutty Prihandani (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2019)
Glycated Hb (HbA1c) test is needed to control glycemic in high prevalence type 2 Diabetes Mellitus (DM) patients. Hemoglobin fraction separated and chemical reaction is two main concepts in the HbA1c test. Ion exchange-high performance liquid chromatography (HPLC) and boronate affinity use the first concept. Ion exchange-HPLC is a reference method in most of the clinical laboratory. Point of care testing (POCT) with boronate affinity method that has been standardized by the international institution is available. This study aimed to compare the boronate affinity POCT method and ion exchange-HPLC method. This cross-sectional study was conducted to 22 types 2 DM patients those fulfilled inclusion and exclusion criteria in January 2017 to February 2018. Level of HbA1c was assayed with boronate affinity POCT and ion exchange-HPLC method. A t-test was used to analyze data and no significant difference if p>0.005. Subjects of this study are females (59.1%) more than males (40.9%) with age mean 59.23 years old (8.1). Uncontrolled type 2 DM (77.3%) more than controlled type 2 DM (22.7%).Mean of HbA1 level was 8.0% (1.7) in boronate affinity POCT and 8.3% (1.8) in ion exchange-HPLC. T-test showed no significant difference between those two HbA1C assay methods (p>0.005). There was no difference HbA1c level between boronate affinity POCT method and ion exchange-HPLC method.